Longevity of a brain-computer interface for amyotrophic lateral sclerosis - Vansteensel, MJ; Leinders, S; Branco, MP; Crone, NE; Denison, T; Freudenburg, ZV; Geukes, SH; Gosselaar, PH; Raemaekers, M; Schippers, A; Verberne, M; Aarnoutse, EJ; et al. (Massachusetts Medical Society, 2024)
The durability of communication with the use of brain-computer interfaces in persons with progressive neurodegenerative disease has not been extensively examined. We report on 7 years of independent at-home use of an implanted brain-computer interface for communication by a person with advanced amyotrophic lateral sclerosis (ALS), the inception of which was reported in 2016. The frequency of at-home use increased over time to compensate for gradual loss of control of an eye-gaze-tracking device, followed by a progressive decrease in use starting 6 years after implantation. At-home use ended when control of the brain-computer interface became unreliable. No signs of technical malfunction were found. Instead, the amplitude of neural signals declined, and computed tomographic imaging revealed progressive atrophy, which suggested that ALS-related neurodegeneration ultimately rendered the brain-computer interface ineffective after years of successful use, although alternative explanations are plausible. (Funded by the National Institute on Deafness and Other Communication Disorders and others; ClinicalTrials.gov number, NCT02224469.).